2018
DOI: 10.1002/ange.201801999
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Dynamic Folding and Unfolding of RNA G‐Quadruplexes in Live Cells

Abstract: Because of the absence of methods for tracking RNA G-quadruplex dynamics,e specially the folding and unfolding of this attractive structure in live cells,u nderstanding of the biological roles of RNAG -quadruplexes is so far limited. Herein, we report an ew red-emitting fluorescent probe, QUMA-1,f or the selective,c ontinuous,a nd real-time visualization of RNAG-quadruplexes in live cells.The applications of QUMA-1 in several previously intractable applications, including live-cell imaging of the dynamic foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
(13 reference statements)
1
50
0
Order By: Relevance
“…QUMA 1w as ah it that selectively stained RNA in HeLa cells duringa ne nzyme-digestion-based screening of an in-house compound library (Figure 10 c). [66] The hit compound exhibited desired (or more) properties that allowed the visualization of RNA G4 dynamics in live cells. ISCH-nras was uniquely developedf or the detection of ap articularR NA quadruplex (NRAS), based on the hybridization of at ail RNA sequence adjacent to aG -rich sequenceb yaDNA molecule connected to aq uadruplex-triggered fluorescent probe (Figure 10 d).…”
Section: Specific Targeting Of Telomere G4smentioning
confidence: 99%
See 1 more Smart Citation
“…QUMA 1w as ah it that selectively stained RNA in HeLa cells duringa ne nzyme-digestion-based screening of an in-house compound library (Figure 10 c). [66] The hit compound exhibited desired (or more) properties that allowed the visualization of RNA G4 dynamics in live cells. ISCH-nras was uniquely developedf or the detection of ap articularR NA quadruplex (NRAS), based on the hybridization of at ail RNA sequence adjacent to aG -rich sequenceb yaDNA molecule connected to aq uadruplex-triggered fluorescent probe (Figure 10 d).…”
Section: Specific Targeting Of Telomere G4smentioning
confidence: 99%
“…Cell‐based screening of G4 ligands, as mentioned previously, was also effective in this case. QUMA 1 was a hit that selectively stained RNA in HeLa cells during an enzyme‐digestion‐based screening of an in‐house compound library (Figure c) . The hit compound exhibited desired (or more) properties that allowed the visualization of RNA G4 dynamics in live cells.…”
Section: Addressing the Specificity Of Ligands To Particular G4smentioning
confidence: 99%
“…G-quartets in G4s are additionally stabilized by monovalent cations, in which Li + < NH4 + < Na + < K +1 . RNA G4s (rG4s) have previously been visualized in both fixed and live cells using G4-specific antibodies and G4-specific fluorescence probes 47 . Numerous studies have suggested that rG4s regulate processes such as transcription, RNA splicing, translation and RNA metabolism 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, to verify the Mito‐Cy‐involved mitochondria viscosity imaging, the fluorescence imaging experiments of Mito‐Cy‐stained MCF‐7 cells have been explored by introducing nystatin that increases the mitochondrial viscosity, or DNase I that degrades the intracellular DNA . Our mitochondria‐localized Mito‐Cy probe exhibits obvious red fluorescence enhancement in nystatin‐pretreated MCF‐7 cells, yet it shows negligible fluorescence changes after treatment with DNase I (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%